Proceedings of 1995 Conference on Electrical Insulation and Dielectric Phenomena
DOI: 10.1109/ceidp.1995.483772
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ac voltage on charge density in a spacer

Abstract: The charging of acrylic glass rod under the influence of ac voltage is reported. A linear dependence of the accumulated charge density on the peak ac applied voltage is observed. A comparison between the accumulated charge density with ac and dc applied voltages is reported. The charge densities that accumulate under the effect of ac voltage are smaller than under dc voltage for the same peak voltage level. A switchable dc power supply to simulate an ac voltage application is also employed. Results show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Experimental data reported in [20] on the application of realistic ac electrical gradients to an indating specimen verify the previous assumption. Voltage application of ac resulted in surface charge build-up.…”
Section: Discussionsupporting
confidence: 69%
“…Experimental data reported in [20] on the application of realistic ac electrical gradients to an indating specimen verify the previous assumption. Voltage application of ac resulted in surface charge build-up.…”
Section: Discussionsupporting
confidence: 69%
“…He found that charge accumulation under the AC stress is favourably of the negative polarity with lower amplitude compared with the case measured under DC application. Studies of Elkhodary and Hackam [13] suggest that positive and negative charges maybe neutralised repeatedly during the positive and negative half waves of AC voltage. Owing to the polarity effect of micro‐discharge, and the higher mobility of electron than that of ion, negative charges take a priority on the insulator surface.…”
Section: Introductionmentioning
confidence: 99%